2020
DOI: 10.1002/mdc3.13121
|View full text |Cite
|
Sign up to set email alerts
|

Central Cognitive Processing Speed Is an Early Marker of Huntington's Disease Onset

Abstract: Background Background: Several studies have suggested that cognitive processing speed may be useful for assessing early cognitive change in premanifest Huntington's disease (HD); however, current measures lack the ability to control for the effects of motor dysfunction commonly found in HD. The Computerized Test of Information Processing (CTiP) is a rapidly administered computerized tool that allows for the examination of central cognitive processing speed by using motor-corrected scores to account for motor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Finally, we note that impairments in executive functioning or semantic verbal skills may contribute to the quantification of bradyphrenia in our study. Our previous analysis of cognitive processing in HD, as measured by the CTiP, displayed greater reaction times for the CRT compared to the SRT, suggesting that this increase is not purely due to differences in semantic verbal skills [9] ; however, further research into bradyphrenia would benefit from the inclusion of additional levels of cognitive difficulty.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Finally, we note that impairments in executive functioning or semantic verbal skills may contribute to the quantification of bradyphrenia in our study. Our previous analysis of cognitive processing in HD, as measured by the CTiP, displayed greater reaction times for the CRT compared to the SRT, suggesting that this increase is not purely due to differences in semantic verbal skills [9] ; however, further research into bradyphrenia would benefit from the inclusion of additional levels of cognitive difficulty.…”
Section: Discussionmentioning
confidence: 84%
“…We have previously shown that deficits in central cognitive processing, as measured by the CTiP CRT-SRT and SSRT-SRT measures, become apparent during the prodromal and manifest HD stages [9] . The present study builds on these findings, by showing that the within-group reaction time differences between choice (CRT-SRT) and semantic search (SSRT-SRT) responses, corrected for motor performance, increase with HD disease stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations